Analisis Sistem Penempatan Pegawai Pada Badan Kepegawaian Daerah Kabupaten Enrekang - Sila, Nursafitry; Mappamiring, Mappamiring; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This stud aims to determine how to analyse the employee placement system in the regional civil service egency Enrekang district. This type of research uses descriptive qualitative the number of informants in this study was 5 people. Date collection techniques are date reduction, interviews and documentation. Date analysis techniques are date reduction, data percentation and conclusion drawing. The results showed that the analysis of the employee placement system was ineffective, because there were still many employee placement system was in efecctive, because there were still many employee who were not in accordance with their educational background , work knowledge, and job skills. This is influenced by factors in employees placement, namely the expansion of the organization, leaving, retiring and passing away.Keywords: employee placement, regional civil service again